Complete Genome Sequences of Enterococcus rotai LMG 26678(T) and Enterococcus silesiacus LMG 23085(T) - Lauer, Ana C. (Genome Announc, 2016)
The inclusion of molecular methods in the characterization of the novel species Enterococcus horridus necessitated the sequencing and assembly of the genomes of the closely related Enterococcus rotai and Enterococcus silesiacus. Sequencing using Illumina technology in combination with optical mapping led to the generation of closed genomes for both isolates.